2019
DOI: 10.1002/navi.340
|View full text |Cite
|
Sign up to set email alerts
|

Joint navigation performance of distant retrograde orbits and cislunar orbits via LiAISON considering dynamic and clock model errors

Abstract: Distant retrograde orbits (DROs) in cislunar space offer a promising option for providing navigation services to satellites in the Earth-Moon system due to their long-term orbital stability and unique three-body orbital dynamics. The Linked Autonomous Interplanetary Satellite Orbit Navigation (LiAISON) technique is used to process the satellite-to-satellite tracking (SST) range measurements between a DRO satellite and another satellite in cislunar space to determine their absolute orbital states. The paper eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In addition to the effect of observations, modeling errors and filtering methods have also been studied so far. The high fidelity measurement models are used for distance retrogate orbiter in cislunar space to see the effect of satellite-borne clock errors [123]. Lastly, novel filtering methods are also studied for the LiAISON architecture in [124].…”
Section: Crosslink Radiometric Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effect of observations, modeling errors and filtering methods have also been studied so far. The high fidelity measurement models are used for distance retrogate orbiter in cislunar space to see the effect of satellite-borne clock errors [123]. Lastly, novel filtering methods are also studied for the LiAISON architecture in [124].…”
Section: Crosslink Radiometric Navigationmentioning
confidence: 99%
“…Comprehensive studies have demonstrated the LiAISON algorithm's capabilities over the past decade [8,110,[121][122][123][125][126][127][128]. The general trend is that LiAISON provides excellent results for cases around asteroids and lunar-Lagrangian points and less accurate results for cases in which orbiters are very close to each other and the gravitational body, such as lunar orbiters.…”
Section: Crosslink Radiometric Navigationmentioning
confidence: 99%
“…This method has been applied to mission studies at librations points, asteroids, and cislunar vicinity (A. Hill (2007); Hill & Born (2007); Leonard et al (2012); Hesar et al (2015); Wang et al (2019); Hill et al (2006); Hill & Born (2008); Leonard (2015); Fujimoto et al (2016)). The method will be applied in the CAPSTONE mission (Figure 1) using a crosslink between Lunar Reconnaissance Orbiter (LRO) and the CAPSTONE CubeSat, (NASA (2020b)).…”
Section: Crosslink Radiometric Navigationmentioning
confidence: 99%
“…Considering the asymmetric gravity field in the cislunar vicinity, it is possible to build such an autonomous navigation system. Up to now, various studies have presented the capabilities of LiAISON over the past decade in lunar and deep space mission studies [11,23,12,7,22].…”
Section: Introductionmentioning
confidence: 99%